Organic Compost Production Using the Berkeley Method as an Effort to Control Aquatic Weeds in Lembah Silangit Lake - Syarifah, Risqa Naila Khusna; Azizah, Maulidia Nur; Riyanto, Dwi Wahyu; Abiyuga, Muhammada Afif; Tampubolon, Lisna Hartati; Asri, Mutia Rahma Dwi; Putri, Shalma Erwina; Pradana, Adilla Rachmawati; Romadhon, Gilang Nur; Izzati, Tamara Nur; Saputra, Restu Damar (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
This production of organic compost using the Berkeley method was carried out as an effort to control the excessive growth of aquatic weeds in Lembah Silangit Lake, Patemon Village, Bojongsari District, Purbalingga Regency, which has long disrupted the ecological, aquaculture, and socio-economic functions of the lake. The proliferation of aquatic weeds, triggered by eutrophication, leads to sedimentation, waterway blockages, and decreased fishery productivity. To address this issue, training on organic composting with the Berkeley method was conducted in collaboration with the Tirta Martani Village-Owned Enterprise (BUMDes). The Berkeley method was chosen because it can produce mature compost in a relatively short time, about 2–3 weeks. The results of the activity showed that participants understood the composting techniques and successfully produced quality organic fertilizer from aquatic weeds. In addition to contributing to weed control and the improvement of the lake ecosystem, this activity also opened opportunities for the community to gain economic value through the sustainable use of local resources.